Semiconductor Device Noise Computation Based on the Deterministic Solution of the Poisson and Boltzmann Transport Equations. Issue 1 (1998) - Piazza, Alfredo J.; Korman, Can E.
Abstract : Numerical simulation results of noise due to current fluctuations along ann + − n − n + submicron structure are presented. The mathematical framework is based on the interpretation of the equations describing electron transport in the semiclassical transport model as stochastic differential equations (SDE). According to this formalism the key computations for the spectral density describing the noise process are reduced to a special initial value problem for the Boltzmann transport equation (BTE). The algorithm employed in the computation of the space dependent noise autocovariance function involves two main processes: the stationary self-consistent solution of the Boltzmann and Poisson equations, and a transient solution of the BTE with special initial conditions. The solution method for the BTE is based on the Legendre polynomial method. Noise due to acoustic and optical scattering and the effects of nonparabolicity are considered in the physical model.